Does Appearance Matter? Current Issues and Formulation of a Research Agenda for Moulage in Simulation. Issue 1 (February 2017) - Stokes-Parish, Jessica B.; Duvivier, Robbert; Jolly, Brian
Abstract : Summary Statement: The use of moulage is assumed to add realism and authentic context in simulation. Despite the expense required to utilize moulage effectively, there is little exploration in the literature as to both its necessity and its accuracy of portrayal. We explore engagement, authenticity, and realism theories in the context of moulage and highlight the need for more evidence on moulage in simulation-based education, including suggestions for future research. In particular, we urge the simulation community to move beyond descriptive papers to investigate moulage in terms of justification and clarification.